Patient Waiting Time in Emergency Department of a Tertiary Level Hospital: Waiting time in emergency department - Islam, Md Khorshedul; Khair, Mohammed Abu; Khanam, Fahmida (Journal of Preventive and Social Medicine, 2020)
Background: Patient waiting time is an important factor of utilizing hospital service, patient satisfaction, quality of management etc. Hence, emergency department (ED) performance can be best assessed by measuring patients’ waiting time and affecting factors at this department. Objective: To determine patient waiting time at ED and associated factors in a tertiary level hospital. Materials and methods: This cross sectional study was conducted in ED of Chattogram Medical College & Hospital (CMCH), Bangladesh. A total of 175 patients or their attendants at ED were enrolled by convenient sampling technique. Data were collected by face- to- face interview with pretested semi-structured questionnaire and observational checklist. Descriptive statistics was used for analysis by MS Excel and SPSS 21st version windows software. Result: Around half (47.40%) was male followed by female (32%) and children (20.6%). Mean (± SD) age of the patients was 33.69 ± 21.33 years. More than half (52.6%) were from rural areas followed by urban areas (47.7%). Average monthly family income was Tk. 23891.43(±13033.76). Mean (±SD) waiting time for collecting ticket, consultation with doctor, physical examination, and nursing services were 8.06(±7.98) minutes, 5.46(±6.95) minutes, 2.30(±1.11) minutes and 8(±6.22) minutes respectively. More than two fifth (41.1%) patients had waiting time within 5 minutes. The ratio of doctor/patient, nurse/patient, ticket provider/patient and trolleys & wheel chairs bearer/patient were 1:115, 1:58, 1:115 and 1:40 respectively. Majority of the patients (57.7%) were transferred to Inpatient Department (IPD). Statistically significant relationship was found between satisfaction on overall management and overall waiting time of ED (χ2 = 22.47, df =6, p=0.001). Conclusion: Majority (48.1%) found satisfied with waiting time at the emergency department. JOPSOM 2019; 38(2): 15-21